Spatio-temporal variation of air pollutants and the impact of anthropogenic effects on the photochemical buildup of ozone across Delhi-NCR. (November 2017) - Peshin, S.K.; Sharma, Ashima; Sharma, S.K.; Naja, Manish; Mandal, T.K.
Highlights: Evaluated the ambient air quality of the megacity Delhi India. Air mass trajectories and their residence time analysis quantified the photochemical O3 buildup at the study sites. Maximum air mass stagnancy events were observed during winter season. Analysis confirmed that anthropogenic sources have strong dominance over O3 pollution at the receptor sites. Abstract: Continuous, real time measurements of gaseous and particulate air pollutants (surface ozone (O3 ), NO, NO2, CO, PM2.5 and PM10 ) were carried out during October 2010 to December 2014 within a network of 8 air quality monitoring stations (AQMSs) located over 2000 km 2 across Delhi-NCR. The behavior of the pollutants' mixing ratios in the diverse microenvironments of an urban megacity was examined to comprehend their distribution on various temporal (daily, monthly, seasonal and annual) and spatial scales. Backward air mass trajectories and residence time (RT) analysis helped quantify the amount of photochemical O3 buildup at the study site. Tagging of O3 values with RT revealed significant positive correlations indicating that O3 buildup begins when fresh air masses come into the polluted domain and is accumulated during 1–3 days, producing O3 through photooxidation processes. Following this, less pronounced effects are observed due to saturated and aged air masses, showing reduced photochemistry. Maximum air mass stagnancy events were observed during winters, owing to a suppressed boundary layer with O3 buildup occurring at the rate of 25.8 ppb day −1 during this season. The study found out that large-scale anthropogenic emissions in the surrounding regions had the strongest influence on O3 production within the study site, but long-range transport was a dominant likelihood, especially during the pre-monsoon season.